1996
DOI: 10.1063/1.871727
|View full text |Cite
|
Sign up to set email alerts
|

Plasma channel formation by short pulse laser

Abstract: A short pulse laser propagating through a preformed plasma exerts a radial ponderomotive force on the electrons and creates a low density plasma channel via ambipolar diffusion. If the radial intensity profile of the laser beam is clamped, i.e., assumed Gaussian in r with fixed half-width r0, then closed form analytic solution of the evolution of plasma density in the channel is obtained in the perturbation approximation, Δn≪n0, where Δn is the modification in electron density over its equilibrium value n0, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Under the action of the ponderomotive force, electrons and ions move together at the ion sound speed c s ; thus, the characteristic time for the manifestation of the ponderomotive nonlinearity is r 0 /c s , where r 0 is the beam width. Additional phenomena contributing to the (de)focusing of an electromagnetic beam in a plasma are multiphoton (tunnel) ionization (Annou et al, 1996), avalanche ionization (Stuart et al, 1996;Derenzo et al, 1974), harmonic generation (Sodha & Kaw, 1969), modification (Gurevich, 1978) of electron density, and nonlinear absorption (Sharma et al, 2004). All these forms of nonlinearity are present and operate in various relative strengths in different regimes in terms of the irradiance, electron density, electron collision frequency, and duration of the pulse of the beam.…”
Section: Introductionmentioning
confidence: 98%
“…Under the action of the ponderomotive force, electrons and ions move together at the ion sound speed c s ; thus, the characteristic time for the manifestation of the ponderomotive nonlinearity is r 0 /c s , where r 0 is the beam width. Additional phenomena contributing to the (de)focusing of an electromagnetic beam in a plasma are multiphoton (tunnel) ionization (Annou et al, 1996), avalanche ionization (Stuart et al, 1996;Derenzo et al, 1974), harmonic generation (Sodha & Kaw, 1969), modification (Gurevich, 1978) of electron density, and nonlinear absorption (Sharma et al, 2004). All these forms of nonlinearity are present and operate in various relative strengths in different regimes in terms of the irradiance, electron density, electron collision frequency, and duration of the pulse of the beam.…”
Section: Introductionmentioning
confidence: 98%
“…Liu and Tripathi (1994) have examined the selfdefocusing of ionizing short laser pulse and laser guidance in the inhomogeneous tunnel ionized plasma channel. The theory of plasma expansion under the influence of the ponderomotive force due to inhomogeneous laser intensity profile has been developed by Annou et al (1996). Deng et al (2003) have studied the effect of tunnel ionization on the wakefield generation and concluded that the influence of tunnel ionization cannot be ignored for short laser pulses.…”
Section: Introductionmentioning
confidence: 99%
“…They have also examined the propagation of the laser main pulse, in the steady state, through the inhomogeneous plasma channel created by the prepulse. Annou and Tripathi 12 have developed a theory of plasma expansion under the ponderomotive force of a laser.…”
Section: Introductionmentioning
confidence: 99%